Analisis proses pengendalian kualitas produk X menggunakan metode Fault Tree Analysis (FTA) pada PT XYZ - Imam, Saeful; Muryeti, Muryeti; Prihandini, Anisa Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Packaging X is a folding carton packaging that has many product defects that do not meet predetermined standards, with an average defect of 19.40% during the period March 2023 to February 2024, exceeding the company's tolerance target of 3%. This study aims to identify the types of defects and the factors that cause them, as well as to provide suggestions for improvements related to the problem of product defects. The method used in this research is the Fault Tree Analysis method with pareto diagram analysis. The results showed six types of defects in X packaging, including light color (6.7%), flooding (17.2%), bulky color (5.8%), glue bleber (55%), wrinkle (8.6%), and powder (6.7%). Based on the fault tree diagram, there are 5 (five) top events, namely humans, machines, materials, methods, and the environment. The proposed improvements are creating new work standards, modifying packaging design, improving supervision, asking maintenance to monitor machine conditions, repairing blisters and preparing spare parts stock, wrapping paper with wrap, improving machine stability control, and scheduling machine area cleaning.